Breaking Ground in Skill Assessment: The Construction and Validation of a Problem-Solving Scale for University Students - Kholili, Ma'rifatin Indah; Asrowi, A; Susilo, Agus Tri (Universitas Negeri Padang, 2023)
Students today is expected to possess 21st-century skills, one of which is Problem Solving Skills (PSS). The importance of mastering this skill needs to be accompanied by the availability of a measuring tool. This research addresses this need by developing and validating the Problem-Solving Skill Scale. The development of this scale is focused on guidance and counseling students. The research and development of this instrument follow the educational design research method according to Plomp and Nieveen. Four hundred students were involved to test the construct validity. Problem-solving skills were measured based on three aspects: (1) Problem-Solving Confidence, (2) Approach-Avoidance Style, (3) Personal Control. Data were analyzed using the Rasch model by the WinSteps software. The research results describe the instrument's quality, the person-item interaction , the item difficulty level (item measures), fit and misfit items, and the distribution of respondents' abilities and the distribution of item levels on the same scale, and the scale’s ability to measure what it intends to measure. The Rasch analysis results show that the PSS Scale is good, precise, and has item fit with the model. The PSS Scale is a valid and reliable measuring tool for accurately measuring students' problem-solving skills. This research discusses implications and recommendations for further research efforts to facilitate the improvement of problem-solving skills in students using this measurement tool.